2021
DOI: 10.1016/j.ebiom.2021.103510
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics based multi-dimensional characterization and drug screen in esophageal squamous cell carcinoma

Abstract: Background Esophageal squamous cell carcinoma (ESCC) remains one of the deadly cancer types. Comprehensively dissecting the molecular characterization and the heterogeneity of ESCC paves the way for developing more promising therapeutics. Methods Expression profiles of multiple ESCC datasets were integrated. ATAC-seq and RNA-seq were combined to reveal the chromatin accessibility features. A prognosis-related subtype classifier (PrSC) was constructed, and its associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 108 publications
(143 reference statements)
0
16
0
Order By: Relevance
“…Specifically, lymphocyte activation gene-3 (LAG3) may be a potential target for immunotherapy [ 65 ]. Furthermore, by combining the Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq) data with RNA-seq data of EC patients, Li et al uncovered the potential transcriptional regulation characterization and constructed a LASSO-based prognosis-related subtype classifier, which is associated with TME heterogeneity and immunotherapy responses [ 66 ].…”
Section: New Insights Into Cancer Immunotherapy Based On Ai-assisted ...mentioning
confidence: 99%
“…Specifically, lymphocyte activation gene-3 (LAG3) may be a potential target for immunotherapy [ 65 ]. Furthermore, by combining the Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq) data with RNA-seq data of EC patients, Li et al uncovered the potential transcriptional regulation characterization and constructed a LASSO-based prognosis-related subtype classifier, which is associated with TME heterogeneity and immunotherapy responses [ 66 ].…”
Section: New Insights Into Cancer Immunotherapy Based On Ai-assisted ...mentioning
confidence: 99%
“…Several recent studies have explored the gene expression profile of ESCC in view of identifying some genes whose expression is prognostic. Thus, Li et al explored the expression profiles of multiple ESCC datasets and, through the integration of these profiles, identified six upregulated genes (HEATR1, TIMELESS, DTL, RUVBL1 and ECT2), which were found to be highly important in ESCC survival; the alterations in the expression of four genes (PRIM2, HGPD, NELL2 and RFAP28) were associated with changes in chromatin accessibility [50]. The authors next explored intertumor heterogeneity and, using a regression and prognosis-related classifier, identified two tumor subtypes, S1 and S2, distinguished according to their outcomes and gene expression profiles.…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…Application of CellChat to scRNA-seq data of esophageal squamous cell carcinoma (ESCC) highlighted the role of TNS1high fibroblasts in TME, in particular the interaction with cytotoxic T cells. Of note, TNS1high fibroblasts was associated with immune exclusion phenotype and poor prognosis of ESCC patients [ 61 ]. CellPhoneDB was applied to systematically study interactions within the TME in murine melanoma and identified stromal-immune interactions, such as C3–C3AR1, CXCL12–CXCR4 and CSF1–CSFR1 with macrophages as primary target [ 62 ].…”
Section: Biological Insights Gained By Cell–cell Communication Analys...mentioning
confidence: 99%